2019
DOI: 10.1016/j.ajhg.2019.08.002
|View full text |Cite|
|
Sign up to set email alerts
|

Distinct HLA Associations with Rheumatoid Arthritis Subsets Defined by Serological Subphenotype

Abstract: Rheumatoid arthritis (RA) is the most common immune-mediated arthritis. Anti-citrullinated peptide antibodies (ACPA) are highly specific to RA and assayed with the commercial CCP2 assay. Genetic drivers of RA within the MHC are different for CCP2-positive and -negative subsets of RA, particularly at HLA-DRB1. However, aspartic acid at amino acid position 9 in HLA-B (B pos-9 ) increases risk to both RA subsets. Here we explore how individual serologies associated with RA drive association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…Other ACPA did not co-occur to the same extent, which may suggest different triggering mechanisms for different ACPA finespecificities. This, we have recently explored in a separate study, demonstrating unique genetic characteristics for different ACPA fine-specificities [36]. We did not find an association between HLA-DRB1 SE and RF in anti-CCP2-negative RA, supporting data generated from single-cell RNA sequencing of RF-positive and ACPApositive B cells, which suggest a T cell-dependent affinity maturation for the generation of ACPA, but innate immune pathways for the generation of RF [37].…”
Section: Discussionsupporting
confidence: 69%
“…Other ACPA did not co-occur to the same extent, which may suggest different triggering mechanisms for different ACPA finespecificities. This, we have recently explored in a separate study, demonstrating unique genetic characteristics for different ACPA fine-specificities [36]. We did not find an association between HLA-DRB1 SE and RF in anti-CCP2-negative RA, supporting data generated from single-cell RNA sequencing of RF-positive and ACPApositive B cells, which suggest a T cell-dependent affinity maturation for the generation of ACPA, but innate immune pathways for the generation of RF [37].…”
Section: Discussionsupporting
confidence: 69%
“…The use of this aa-and antigen-binding grovecentric analysis was further utilized to analyse whether there was any preference for certain variants in the antigen-binding groves and presence of antibody reactivity to different citrullinated peptides. A recent analysis using this approach indeed demonstrated that aspartic acid in position 9 of HLA-B preferably associated with RA subsets defined by the presence of antibodies against distinct citrullinated peptides (defined as 'noncanonical' specificities), whereas valine in position 11 of the HLA-DR beta chain associated with the presence of a large group of mostly cross-reactive antibodies against several citrullinated peptides and proteins (defined as 'canonical' specificities) [50]. When this analysis of serologically defined subsets was extended to the anti-CCP-negative subset, it was also shown that a small group of individuals positive for antibodies against certain fibrinogen, vimentin and enolase-derived citrullinated peptides associated with HLA-DR SE alleles [20].…”
Section: Geneticsmentioning
confidence: 99%
“…A diagnosis of early "seronegative" RA, in this context defined as a lack of both RF and ACPA, may be particularly challenging. This "serological gap" [23] may progressively be closed by antibodies to post-translationally modified antigens such as antibodies to citrullinated or carbamylated proteins [9,10,24] and by the identification of hitherto unrecognized unmodified autoantigenic targets, as we and others have previously shown [12,13,18,25].…”
Section: Discussionmentioning
confidence: 98%
“…As a consequence, efforts have been undertaken to close the "serological gap" of RA diagnosis by various strategies. For instance, tuning of fine specificities of the ACPA assays, potentially also including non-canonical citrullinated antigens, was recently shown to carry the potential for increased RA detection rates [9,10]. Moreover, the inclusion of different isotypes of ACPA alters diagnostic properties and shows potential in seronegative patients [11].…”
Section: Introductionmentioning
confidence: 99%